Decomposing the afternoon effect: An empirical investigation of sequential train ticket auctions - Ola Andersson; Tommy Andersson (Research Institute of Industrial Economics (IFN), 2015)
The afternoon effect, i.e., that prices in a sequence of auctions with identical items are decreasing with the order in which the auctions are terminated, is a frequently observed phenomenon in empirical auction studies. Using an unsurpassed amount of data from sequential online train ticket auctions, we investigate two hitherto unexplored dimensions inherent in sequential auctions, namely, the timing of auction ends and the presentation order of the auctions in a sequence. We find that both these dimensions are important for price formation in sequential auctions, but even when controlling for them, a sizable afternoon effect remains.
Keywords: D02; D44; 330; sequential auctions; afternoon effect; presentation order; timing